Running Anaerobic Sprint Test, Lactate Minimum and Critical Velocity Protocol in Shuttle Futsal Testing - Tiago Buzatto de Lima; Vinícius Carvalho de Andrade; Leonardo Henrique Dalcheco Messias; Fúlvia de Barros Manchado-Gobatto; Ramon Martins de Oliveira; Ricardo Alexandre Rodrigues Santa Cruz; KauêTomazine Rosante (Central European Journal of Sport Sciences and Medicine, 2015)
The aims of this study were to investigate whether the running anaerobic sprint test, lactate minimum and critical velocity protocol can be applied in shuttle futsal testing, and to investigate if these protocols provide related variables. Seven male welltrained futsal players were evaluated. The lactate minimum test (LacMin) consisted of three phases: a) a hyperlactatemia phase using the running anaerobic sprint test (RAST); b) recovery phase; c) an incremental shuttle test for the lactate minimum speed (LMS) determination. Successful rate (SR) was calculated for feasibility analysis. Peak, mean and minimum power and fatigue index were obtained by the RAST application (six bouts – 35 meters). The critical velocity protocol (CV) was applied through three exhaustive shuttle tests (12, 13 and 14 km/h) with distances of 20 meters. Critical velocity (Cv) and anaerobic running capacity (ARC) were analysed by the linear (velocity vs.1/tlim) and hyperbolic (time vs.velocity) models. Fits of regression (R²) were considered as the main result for feasibility analysis of CV. ANOVA showed a difference between linear (11.04 ±0.55 km/h) and LMS (9.67 ±0.50 km/h), and no significant correlation was observed between them. High SR (85.71%) was observed for LacMin, and high R² for CV (linear-R² = 0.99 ±0.04; hyperbolic-R² = 0.98 ±0.02).Overall, the RAST, LacMin and CV can be successfully applied in shuttle futsal testing, nonetheless, precaution is necessary since the test results were not related.